Determination of IGF-1-producing CHO-K1 growth phases using GCMS-based global metabolite analysis - Saberi, S.E.M.; Hashim, Yumi Zuhanis Has-Yun; Mohamed, V.Packeer; Mel, Maizirwan; Ahmad Raus, Raha; Amid, Azura (IIUM Press, 2011)
Mammalian cell lines, in particular CHO-K1 is vital for the multibillion dollar biotechnology industry. The majority of large scale bioprocessing of commercially aluable protein biopharmaceuticals is produced using this type of cell. An ideal mammalian cell system as host for biologics production should retain efficient use of energy sources in order to boost productivity at minimum cost. Various analyses such as cell counting and monitoring of specific biochemical responses are used to provide data to enable bioprocess control in order to achieve the ideal system. Our study aimed to see whether global metabolite analysis using Gas Chromatography Mass Spectrometry (GCMS) would be a potential alternative approach in providing data for bioprocess control. In this study, we analyzed metabolites of CHO-K1 cells at different growth phases using GCMS. CHO-K1 cells producing insulin like growth factor-I (IGF1) were obtained from ATCC. Cells were grown in T-flask and incubated at 37°C/ 5% CO2 until 70-80% confluent in RPMI 1640 media. Samples (cells and spent/conditioned media) were taken at designated intervals for routine cell counting (Trypan Blue dye exclusion method); glucose, glutamine and lactate determination (YSI 2700); IGF-1 production (ELISA kit R&D Sstems, Inc); and global metabolite analysis (GCMS). Conditioned media from each time point were spun down before subjecting into GCMS. Data from GCMS was then transferred to SIMCA P+12.0 for chemometric evaluation using Principal Component Analysis (PCA). The first component, PC1 results was able to explain 36% of the variation of the data with clear separation between exponential phase and other phases (initial and death phase). This suggests that GCMS-based global metabolite analysis has the ability to capture cell growth behaviour and offered insights of factors that may influence the biological system.